1995
DOI: 10.1007/bf00019373
|View full text |Cite
|
Sign up to set email alerts
|

Hydroacoustic monitoring of the distribution, density and the mass-removal of pelagic fish in a eutrophic lake

Abstract: A large scale biomanipulation of pelagic fish by trawling was started in the eutrophic Enonselka basin (26 km 2 ) of Lake Vesijdrvi to improve the water quality which had remained poor in spite of the termination of nutrient loading . The distribution and density of the fish were studied by hydroacoustics before and during the removal . The initial annual fish density varied between 13 000-21 000 fish ha -' in the study area in August 1984-89 . The mass-removal of the fish by pelagic trawling took place in 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The increased proportion of multiple targets in deeper strata also could be related to a higher probability of including multiple echos as single targets because the critical target density, above which EC gives biased results, decreases as the square of the distance from the transducer (MacLennan and Simmonds 1992). The observed sharp vertical changes in bubble abundance with distance from the bottom indicates that the assumption about similarity of bubble densities in the hypolimnion and epilimnion, which frequently has been used for calculation of fish abundance using hydroacoustic techniques (e.g., Jurvelius and Sammalkorpi 1995), cannot be implemented without testing.…”
Section: Resultsmentioning
confidence: 99%
“…The increased proportion of multiple targets in deeper strata also could be related to a higher probability of including multiple echos as single targets because the critical target density, above which EC gives biased results, decreases as the square of the distance from the transducer (MacLennan and Simmonds 1992). The observed sharp vertical changes in bubble abundance with distance from the bottom indicates that the assumption about similarity of bubble densities in the hypolimnion and epilimnion, which frequently has been used for calculation of fish abundance using hydroacoustic techniques (e.g., Jurvelius and Sammalkorpi 1995), cannot be implemented without testing.…”
Section: Resultsmentioning
confidence: 99%
“…In our gillnetting, seining, trawling and hydroacoustics sampling the effect of daylight hours and water temperature on fish movements was taken into consideration in the sampling design (e.g. Jurvelius & Heikkinen, 1988;Jurvelius & Sammalkorpi, 1995). The results showed that in large lakes the fish community data obtained and the conclusions drawn from it are strongly affected by the sampling method.…”
Section: Discussionmentioning
confidence: 97%
“…Jurvelius and Sammalkorpi, 1995;Horppila et al, 1996;Turunen et al, 1997;Peltonen et al, 1999). In very few occasions, e.g.…”
Section: Introductionmentioning
confidence: 98%